Applying De Morgan's Laws to (A ∨ ¬B) yields ¬(¬A ∧ B), satisfying the specified format and maintaining logical equivalence.
De Morgan's Laws provide a set of logical equivalences involving the negation, conjunction, and disjunction of propositions. The two laws are as follows:
1. ¬(A ∧ B) ≡ ¬A ∨ ¬B
2. ¬(A ∨ B) ≡ ¬A ∧ ¬B
Now, let's apply De Morgan's Laws to the given statement A ∨ ¬B:
¬(A ∨ ¬B) ≈ ¬A ∧ ¬(¬B)
Since ¬(¬B) is equivalent to B, we can simplify further:
¬(A ∨ ¬B) ≈ ¬A ∧ B
Therefore, A ∨ ¬B is equivalent to ¬A ∧ B.
Now, let's express this result using the specified format:
¬(¬A ∧ B)
This expression is in the required format and adheres to the rules stated.